Seminar Pekerja Migran untuk Pencegahan Modus Kerja di Luar Negeri - Roifatur Risma; Nourma Puspa Hidayati; Fitria Susilowati (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
This study evaluates the effectiveness of the Indonesian Migrant Workers (PMI) seminar in raising community awareness in Putatgede Village. The seminar, which involved socialization and interactive discussions, successfully provided relevant information on migrant worker recruitment procedures, the risk of fraud, and protection for migrant workers. The active participation of participants from various age groups showed the high interest of the community in obtaining accurate information. Evaluation results showed an increase in participants' understanding of the importance of working through official channels and vigilance against unclear job offers.